Early Detection Of Hypertension As An Effort To Prevent Disease Complications - Santy Irene Putri; Aris Widiyanto; Joko Tri Atmojo; Asruria Sani Fajriah (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: Measuring blood pressure is one way of early detection of the risk of hypertension, stroke and heart disease. Generally, in rural areas have lower access to health information and education than those in urban areas. Promotive and preventive efforts needed to increase public awareness to carry out early detection through measuring blood pressure regularly and adherence to taking medication regularly. This step is believed to be a form of controlling hypertension in the form of reducing the number of cases, complications, and deaths from hypertension. Methods: The method of activity to be carried out is a health check by measuring blood pressure and providing counseling which is carried out through lectures and discussions with the community about the signs and symptoms of hypertension, prevention of hypertension, and complications of hypertension. The activity was carried out on April 10, 2021 with the target of all members of the community in Wonosuko, Magelang, Central Java. Results: This activity was attended by a community of about 40 people. The implementation of this service went smoothly and the community was enthusiastic in examination and counseling activities. Most of the community felt the benefits of holding this activity because according to them, apart from getting knowledge about hypertension, the community also felt the benefits of checking blood pressure, and consulting various diseases related to complications due to hypertension. Conclusion: This community service activity has added insight and knowledge of communities about hypertension, especially about clinical symptoms, complications and also efforts to prevent hypertension. In addition, the public has also become more aware of the need to have their blood pressure checked at local health care facilities. In addition, communities' knowledge has also increased about several complications of hypertension which have been explained through consultation with the team of this activity.